"We should be resourcing their liberation:" a qualitative formative study to guide introduction of a systems engineering intervention at a King County, WA juvenile detention center clinic - Madeline Borges; Lois Schipper; George Gonzalez; Sean Goode; Dorene Hersh; Do-Quyen Pham; Ben Kaplan; Keshet Ronen; Kenneth Sherr; Sarah Gimbel (BMC, 2023)
Abstract Background There are ongoing efforts to eliminate juvenile detention in King County, WA. An essential element of this work is effectively addressing the health needs of youth who are currently detained to improve their wellbeing and reduce further contact with the criminal legal system. This formative study sought to inform adaptation and piloting of an evidence-based systems engineering strategy - the Systems Analysis and Improvement Approach (SAIA) - in a King County juvenile detention center clinic to improve quality and continuity of healthcare services. Our aims were to describe the priority health needs of young people who are involved in Washington's criminal legal system and the current system of healthcare for young people who are detained. Methods We conducted nine individual interviews with providers serving youth. We also obtained de-identified quantitative summary reports of quality improvement discussions held between clinic staff and 13 young people who were detained at the time of data collection. Interview transcripts were analyzed using deductive and inductive coding and quantitative data were used to triangulate emergent themes. Results Providers identified three priority healthcare cascades for detention-based health services-mental health, substance use, and primary healthcare-and reported that care for these concerns is often introduced for the first time in detention. Interviewees classified incarceration itself as a health hazard, highlighting the paradox of resourcing healthcare quality improvement interventions in an inherently harmful setting. Fractured communication and collaboration across detention- and community-based entities drives systems-level inefficiencies, obstructs access to health and social services for marginalized youth, and fragments the continuum of care for young people establishing care plans while detained in King County. 31% of youth self-reported receiving episodic healthcare prior to detention, 15% reported never having medical care prior to entering detention, and 46% had concerns about finding healthcare services upon release to the community. Conclusions Systems engineering interventions such as the SAIA may be appropriate and feasible approaches to build systems thinking across and between services, remedy systemic challenges, and ensure necessary information sharing for care continuity. However, more information is needed directly from youth to draw conclusions about effective pathways for healthcare quality improvement.